The Recontigencies of Merapi Eruption Disasters in Implementation of Sister Village - oktradiksa, ahwy -; Sari, Kanthi Pamungkas; Setiawan, Agus -; -, Priyo - (Journal of Community Services and Engagement, 2020)
The objectives of PPDM are: 1) Improving the community's understanding of the community-based village communication and information system in the implementation of sister villages and the follow-up phase will be carried out gradually and continuously. 2) Build an organizational or institutional structure that functions to handle disasters so that they are better planned and clear. 3) Develop technical guidelines as put-off Buffer Village in sister village implementation. 4) Promote joint activities to improve the hospitality of KRB III Village and Buffer Village. The method to be used in achieving these goals is a participatory Rural Appraisal (PRA) participatory community empowerment model. The results obtained: 1) Management of Deyangan Village Disaster Management Institution is more organized and in implementing sister village implementation together with Krinjing Village has a meaningful agreement to mitigate the eruption of Mount Merapi, 2) The Village of Buffer has more adequate MCK facilities in case of displacement at any time so that problems that will arise in the health aspects of refugees will be minimized, especially in clean and healthy lifestyles, 3) Deyangan Village has more adequate internet towers to improve the quality of communication and information as a sister village and support the development of SID, 4) Villages KRB III and the Village of Buffer seek joint activities to increase friendship to hold a "Village Cultural Potential Expo (Sister Village).